Radiation Interception, Chlorophyll Fluorescence and Senescence of Flag leaves in Winter Wheat under Supplemental Irrigation - Man, Jianguo (Sci Rep, 2017)
Water shortage threatens agricultural sustainability in China, effective water-saving technologies urgently need to be developed. In this study, five treatments were conducted: rainfed (W0), a local supplemental irrigation (SI) practice (W1), and three treatments in which soil water content was tested prior to SI, specifically at 0–20 (W2), 0–40 (W3) and 0–60 cm (W4) soil layers. Soil water consumption in W3 had no differ with W2 but was higher than W1 and W4. Crop evapotranspiration in W1, W3 and W4 treatments were higher than that in W2. W3 treatment had higher leaf area index than W1 and W4 at later grain filling stages. The mean photosynthetically active radiation capture ratio in W3, especially at 20, 40 and 60 cm plant heights, were significantly higher than those in W1, W2 and W4. The chlorophyll content index, actual photosynthetic activities, catalase and superoxide dismutase activities of flag leaves from W3 were the highest after the middle grain filling stages. W3 treatment obtained the highest grain yield (9169 kg ha(−1)) and water use efficiency (20.8 kg ha(−1) mm(−1)) in the two seasons. These benefits likely accrued through created a suitable soil moisture environment in W3 treatment.